Desphospho-uncarboxylated matrix Gla protein is associated with increased aortic stiffness in a general population - Mayer, O; Seidlerová, J; Wohlfahrt, P; Filipovský, J; Vaněk, J; Cífková, R; Windrichová, J; Topolčan, O; Knapen, M H J; Drummen, N E A; Vermeer, C (Journal of human hypertension, 2016)
Matrix Gla protein (MGP), a natural inhibitor of calcification, strongly correlates with the extent of coronary calcification. Vitamin K is the essential cofactor for the activation of MGP. The nonphosphorylated-uncarboxylated isoform of MGP (dp-ucMGP) reflects the status of this vitamin. We investigated whether there is an association between dp-ucMGP and stiffness of elastic and muscular-type large arteries in a random sample from the general population. In a cross-sectional design, we analyzed 1087 subjects from the Czech post-MONICA study. Aortic and femoro-popliteal pulse wave velocities (PWVs) were measured using a Sphygmocor device. Dp-ucMGP concentrations were assessed in freshly frozen samples by enzyme-linked immunosorbent assay methods using the InaKtif MGP iSYS pre-commercial kit developed by IDS and VitaK. Aortic PWV significantly (P<0.0001) increased across the dp-ucMGP quartiles. After adjustment for all potential confounders, aortic PWV independently correlated with dp-ucMGP (with beta coefficient (s.d.) 11.61 (5.38) and P-value=0.031). In a categorized manner, subjects in the top quartile of dp-ucMGP (⩾ 671 pmol l(-1)) had a higher risk of elevated aortic PWV, with corresponding adjusted odds ratio (95% confidence interval) 1.73 (1.17-2.5). In contrast, no relation between dp-ucMGP and femoro-popliteal PWV was found. In conclusion, increased dp-ucMGP, which is a circulating biomarker of vitamin K status and vascular calcification, is independently associated with aortic stiffness, but not with stiffness of distal muscular-type arteries.
Keywords: matrixový protein Gla; lineární modely; onemocnění periferních arterií; upregulace; Phosphorylation; nemoci aorty; logistické modely; Humans; extracelulární matrix - proteiny; Up-Regulation; lidé středního věku; Risk Factors; fosforylace; Multivariate Analysis; Calcium-Binding Proteins; Female; rizikové faktory; Aged; dospělí; ELISA; senioři; lidé; Biomarkers; Enzyme-Linked Immunosorbent Assay; Extracellular Matrix Proteins; Adult; Pulse Wave Analysis; Matrix Gla Protein; Peripheral Arterial Disease; biologické markery; ženské pohlaví; multivariační analýza; analýza pulzové vlny; Aortic Diseases; Male; Middle Aged; Linear Models; proteiny vázající vápník; Czech Republic; Odds Ratio; Cross-Sectional Studies; Vascular Stiffness; Česká republika; mužské pohlaví; odds ratio; průřezové studie; Logistic Models; tuhost cévní stěny